Childhood Ménétriér's Disease: A Rare Cause of Exudative Enteral Protein Loss - Mark R Oliver; Cynthia Trevenen; R Brent Scott (Canadian Journal of Gastroenterology)
A six-year-old boy with Ménétriér's disease, which developed in association with an intercurrent cytomegalovirus (CMV) infection, is presented. This case illustrates the clinical features, natural history and self-limited nature of this rare cause of exudative protein loss in childhood and provides evidence for the association between CMV infection and the pathogenesis of this disorder.